Assessment of Quality Of Life of Chronic Disease Patients Treated With Herbal Medicine at the Ledzokuku Municipal Assembly (LEKMA) Hospital - Engmann, S.T. (University of Ghana, 2019)
Background: Quality of life (QOL) assessment is recommended to better plan and distribute health care resources with the aim of achieving a better quality of life. Chronic diseases adversely affect the quality of life, and there is also generally an increase of herbal medicine use in chronic disease patients. However, it is unclear whether there is a direct link between the use of herbal medicines and quality of life, particularly among patients with chronic diseases. Objective: The main objective of the study was to assess the quality of life of chronic disease patients treated with herbal medicine at the Ledzokuku Municipal Assembly (LEKMA) Hospital using the World Health Organization Quality of Life (WHOQOL-BREF) assessment tool. Methods: A quantitative cross-sectional study was conducted at the herbal clinic of the Ledzokuku Municipal Assembly (LEKMA) Hospital. Consecutive sampling method was used to recruit 129 participants, where all patients who consented to the study were included. Data were collected through the administration of the World Health Organization Quality of Life (WHOQOL-BREF) assessment tool comprising of 26 items, socio-demographic data, and reasons why participants prefer herbal medicine. Data were entered into Microsoft Excel, cleaned and exported to STATA 13 for analysis. The level of significance used was p <0.05. Results: The quality of life from the transformed mean scores of the four domains were good in the physical health (51.33+15.91), psychological health (57.18+15.74), and environmental domain of quality of life (55.72+13.82) but poor in social relationships (50.18+15.44). However, only 44.1% of the respondents rated their overall quality of life (QOL) as good. Patients with stroke were found to have low transformed mean scores of quality of life (QOL) in all four domains. There was a significant association between the QOL and physical health (p<0.05), psychological factors (p<0.05), social relationships: (p=0.029) and environmental factors (p<0.05). The predominant factors that influence the choice of herbal medicine among patients with chronic disease were; minimal side effects of herbal products, efficacy, and cultural beliefs. The positive predictors of quality of life (QOL) were the highest educational level (p= 0.028) and employment status (p= 0.015). Conclusion: The transformed mean scores of quality of life (QOL) in physical health, psychological domain, and the environmental domain was good among patients with chronic conditions at the herbal clinic of Ledzokuku Municipal Assembly (LEKMA) Hospital but poor in the social domain and 44.1% of the respondents rated their overall quality of life (QOL) as good. Keywords: Quality of life, chronic disease, Herbal medicine
MPH.
Keywords: Quality Of Life; Herbal Medicine; Ledzokuku Municipal Assembly (LEKMA) Hospital